Prevention of post‐dural puncture headache: a randomized controlled trial. (20th February 2020) - Salzer, J.; Granåsen, G.; Sundström, P.; Vågberg, M.; Svenningsson, A.
Abstract : Background and purpose: We investigated 952 subjects undergoing diagnostic lumbar puncture (LP) to study the effects of needle size, needle design and stylet reinsertion on the risk of post‐dural puncture headache (PDPH). Methods: This randomized double‐blind study was performed at Umeå University Hospital in Sweden during 2013–2018. Subjects were randomly assigned one of three needles [22 gauge (G) atraumatic, 25G atraumatic and 25G cutting] and stylet reinsertion before needle withdrawal or not. The main outcome measure was PDPH assessed by standardized telephone interview(s) 5 days after the LP, repeated until headache cessation. We used logistic regression to calculate odds ratios (ORs) with 95% confidence intervals (CI) for PDPH. Results: The mean (SD) age was 51.1 (16.7) years and 53.6% were females. The smaller bore (25G) atraumatic needle incurred a lower risk of headache compared with the larger bore (22G) atraumatic needle [22.0% (69/314) vs. 30.2% (98/324); OR, 0.65; 95% CI, 0.45–0.93] and compared with the cutting needle [32.8% (103/314); OR, 0.58; 95% CI, 0.40–0.82]. Reinserting the stylet before needle withdrawal did not reduce the risk of headache. Conclusions: These data suggest that a 25G atraumatic needle is superior to a larger atraumatic needle, and to a same‐sized cutting needle, in preventing PDPH after diagnostic LP. In contrast to one earlier report, this study did not find that stylet reinsertion was effective in preventing PDPH. This study provides class I evidence that a small atraumatic needle decreases the risk of PDPH and that stylet reinsertion does not influence PDPH risk.